Extrusion blow molding - Thielen, Michael (Carl Hanser Verlag, 2021)
This unique book covers the wide spectrum of extrusion blow-molded hollow bodies, which find application for instance in packaging, storage, and transport or channeling of liquids, gases, or bulk materials, as well as for toys, sporting goods, or technical applications in the automotive or household appliances sectors. The necessary information for fundamental understanding of extrusion blow molding technology is provided, making it easy to comprehend the interrelationships during processing and in applications. This practical knowledge is aimed at facilitating the reader's daily work and studies.In addition to various fields of application and manufacturing processes, aspects of product development and possibilities of blow molding simulation are presented. Further sections on peripheral equipment, downstream equipment, and recycling round off the book.- Resumé vydavatel